Cholelithiasis and cholecystectomy increase the risk of gastroesophageal reflux disease and Barrett’s esophagus - Huang, Yu; Cai, Yicong; Chen, Yingji; Zhu, Qianjun; Feng, Wei; Jin, Longyu; Ma, Yuchao (Frontiers in Medicine, 2024)
Background Cholelithiasis or cholecystectomy may contribute to the development of gastroesophageal reflux disease (GERD), Barrett’s esophagus (BE), and esophageal adenocarcinoma (EAC) through bile reflux; however, current observational studies yield inconsistent findings. We utilized a novel approach combining meta-analysis and Mendelian randomization (MR) analysis, to assess the association between them. Methods The literature search was done using PubMed, Web of Science, and Embase databases, up to 3 November 2023. A meta-analysis of observational studies assessing the correlations between cholelithiasis or cholecystectomy, and the risk factors for GERD, BE, and EACwas conducted. In addition, the MR analysis was employed to assess the causative impact of genetic pre-disposition for cholelithiasis or cholecystectomy on these esophageal diseases. Results The results of the meta-analysis indicated that cholelithiasis was significantly linked to an elevated risk in the incidence of BE (RR, 1.77; 95% CI, 1.37–2.29; p < 0.001) and cholecystectomy was a risk factor for GERD (RR, 1.37; 95%CI, 1.09–1.72; p = 0.008). We observed significant genetic associations between cholelithiasis and both GERD (OR, 1.06; 95% CI, 1.02–1.10; p < 0.001) and BE (OR, 1.21; 95% CI, 1.11–1.32; p < 0.001), and a correlation between cholecystectomy and both GERD (OR, 1.04; 95% CI, 1.02–1.06; p < 0.001) and BE (OR, 1.13; 95% CI, 1.06–1.19; p < 0.001). After adjusting for common risk factors, such as smoking, alcohol consumption, and BMI in multivariate analysis, the risk of GERD and BE still persisted. Conclusion Our study revealed that both cholelithiasis and cholecystectomy elevate the risk of GERD and BE. However, there is no observed increase in the risk of EAC, despite GERD and BE being the primary pathophysiological pathways leading to EAC. Therefore, patients with cholelithiasis and cholecystectomy should be vigilant regarding esophageal symptoms; however, invasive EAC cytology may not be necessary.